Study of in-plane magnetic anisotropy of ultrathin epitaxial Fe films grown on vicinal Mo(110) surface - SHVETS, IGOR; MURPHY, SHANE; USOV, VICTOR (My University, 2004)
In situ surface magneto-optical Kerr effect was used in conjunction with scanning tunneling microscopy and low-energy electron diffraction to study the in-plane magnetic anisotropy of ultrathin Fe films on a vicinal Mo(110) substrate. A uniaxial anisotropy with the easy axis of magnetization along the [001] direction was found for this system down to nearly 2 monolayers coverage, contradicting the results of recent theoretical calculations. The easy axis of a step-induced anisotropy coincides with the surface step edges.
PUBLISHED
Keywords: Surface Physics; thin films